Feelings reported by adolescents after food ingestion: a comparative study - Rodrigues, Naíza Carvalho; Santos, Marize Melo dos; Paz, Suzana Maria Rebêlo Sampaio da; Paiva, Adriana de Azevedo; Nogueira, Thaís Rodrigues; Freitas, Betânia de Jesus e Silva de Almendra; Carvalho, Cecília Maria Resende Gonçalves de (ABCS Health Sciences, 2020)
Introduction: Food is closely linked with emotions in a complex relationship. The imaginary and symbolic meaning attributed to food has been little studied and the act of eating needs to be better understood. Objective: To analyze the association of adolescents´ feelings to selected foods. Methods: Cross-sectional study with 995 adolescents from public and private schools in Teresina, PI, Brazil. It was a Supplementary Project to the Brazilian national survey ERICA (Estudo de Riscos Cardiovasculares em Adolescentes). Adolescents had to choose one of the following feelings to selected food: well-being/satisfaction, malaise, no feeling, aversion. For the option aversion, the participant had to indicate if it was related to smell, color, appearance, or taste. Adolescents´ feelings to foods were analyzed by type of school, sex, and age range, using Pearson's chi-square (c²) or Fisher's exact tests. Results: There was significant differences regarding the type of school for the feeling to chocolate (p=0.015); vegetables (p=0.003); leafy greens (p=0.005); healthy sandwich/natural fruit juice (p≤0.001); high fat red meat (p=0.046); fruit/natural fruit juice (p≤0.001). For sex, there was significant difrerences for healthy sandwich/natural fruit juice (p=0.001); beans and rice (p=0.021) and high fat red meat (p=0.005). There was significant differences between age groups for sandwich, chips, soda and ice cream (p=0.018); pasta (p=0.047) and high fat red meat (p=0.021). Well-being predominated in almost all foods and aversion was poorly reported. Conclusion: The results suggest that adolescents' feelings are not directed to specific foods.